LATE FUNERAL CONTEXTS IN LA SALINA, RÍMAC VALLEY - Machacuay, Marco Antonio (1998)
The authors present an advance of the results from the excavations carried out in the archaeological site of La Salina in El Agustino in Lima. This area has a procces of development from the Formative Period until the Inca presence in the valley. The article details the funerary use of the earlier structures after they were left by their owners, and concentrates in the description of an unpublished funerary pattern belonging to the lntermediate Period and Late Horizon in te middle part of the Rimac valley